The Flypaper Effect Phenomena in Regional Expenditure in Districts/Cities of the Special Province of Yogyakarta - Wildhan Farica; Riko Setya Wijaya (PT FORMOSA CENDEKIA GLOBAL, 2023)
This study aims to analyze the phenomenon of the flypaper effect through the influence of Local Own Revenue, General Allocation Funds, Special Allocation Funds, and Profit Sharing Funds on Regional Expenditures in the Regency/City of the Province of the Special Region of Yogyakarta. The data used in this study is secondary data for 2012 – 2021 sourced from the BPS for the Special Region of Yogyakarta and the DJPK of the Indonesian Ministry of Finance. The research method used is the quantitative method and processed with STATA 14. The results of the analysis show that simultaneously and partially the variables Local Own Revenue, General Allocation Funds, and Special Allocation Funds, have a positive and significant effect on Regional Expenditures. While the Revenue Sharing Fund does not affect Regional Expenditure, among the three balance funds of the General Allocation Fund has a major influence on Regional Expenditure. The results also show that there is a flypaper effect phenomenon in the Regional Expenditure of the Regency/City of the Province of the Special Region of Yogyakarta.